2023
DOI: 10.1073/pnas.2216640120
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of embryonicE93expression as a hypothetical driver of the evolution of insect metamorphosis

Abstract: The early embryo of the cockroach Blattella germanica exhibits high E93 expression. In general, E93 triggers adult morphogenesis during postembryonic development. Here we show that E93 is also crucial in early embryogenesis in the cockroach, as a significant number of E93-depleted embryos are unable to develop the germ band under maternal RNAi treatment targeting E93 . Moreover, transcriptomic analysis indicates that E93 depletion results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The only information for ametabolous insects is for Thermobia domestica . Direct hormone measurements ( Figure 2A ), and Kr-h1 transcript levels ( Fernandez-Nicolas et al, 2023 ) indicate that JH levels are low at hatching and remain low throughout juvenile growth and into the adult. In hemimetabolous insects, by contrast, JH titer measurements or Kr-h1 expression data are available for examples of paleopteran (mayflies; Kamsoi et al, 2021 ), polyneopteran (including grasshoppers and cockroaches: Temin et al, 1986 ; Lanzrein et al, 1985 ; Maestro et al, 2010 ) and paraneopteran orders (heteropteran, Konopova et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only information for ametabolous insects is for Thermobia domestica . Direct hormone measurements ( Figure 2A ), and Kr-h1 transcript levels ( Fernandez-Nicolas et al, 2023 ) indicate that JH levels are low at hatching and remain low throughout juvenile growth and into the adult. In hemimetabolous insects, by contrast, JH titer measurements or Kr-h1 expression data are available for examples of paleopteran (mayflies; Kamsoi et al, 2021 ), polyneopteran (including grasshoppers and cockroaches: Temin et al, 1986 ; Lanzrein et al, 1985 ; Maestro et al, 2010 ) and paraneopteran orders (heteropteran, Konopova et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Titers are based on direct measurements or are estimated from Kr-h1 expression. The ametabolous order, Zygentoma, provides the only data for an ametabolous insect, Thermobia ( Figure 2A ; Fernandez-Nicolas et al, 2023 ). Palaeopteran postembryonic data from the mayfly, Cloeon dipterum ( Kamsoi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ametabolous order, Zygentoma, provides the only data for an ametabolous insect, Thermobia (Fig. 2A; Fernandez-Nicolas et al ., 2023). Palaeopteran postembryonic data from the mayfly, Cloeon dipterum (Kamsoi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Thermobia, JH levels are then quite low in the juvenile (Fig. 2A; Fernandez-Nicolas et al ., 2023), indicating that JH is not needed to maintain the juvenile form. Watson (1967) showed that the appearance of scales in its J4 stage is suppressed by JH application, but we have not been able to induce premature scale formation in the J3 stage by treatment of the J1 and J2 stages with 7EP (Truman and Riddiford, unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation